Automated correction and detection of spatial data using ARC/INFO software / Vicky Vincent Aled - Aled, Vicky Vincent (1999)
Arc Macro Language (AML) is part of the ARC/INFO geographic information system (GIS) software. AML provides information about ARC/INFO objects (e.g; coverage) and specific ARC enviroments.